2019
DOI: 10.15359/ru.33-2.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two cytokinins and a growth inhibitor on the in vitro tuberization of two genotypes of Solanum tuberosum L. cvs. Atlantic and Alpha

Abstract: This investigation was carried out to evaluate the effect of two cytokinins: 6-benzilaminopurine (BAP) (6.5 mg l-1) and kinetin (K) (2.5 mg l-1), as well as the growth inhibitor abscisic acid (ABA) (1.0 mg l-1) on the in vitro tuberization capacity of two potato varieties: Atlantic and Alpha. The basal culture medium MS (1962) was used as a control. The responses were different between varieties. In cv. Atlantic, the analysis of the number (NM), weight (WM) and diameter (DM) of microtubers indicated that the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The positive effects of cytokinin on potato tuberization has also been reported by [9] and [10]. Furthermore, in vitro experiment showed that applying a single plant growth regulator (PGR), has been reported to be less effective in inducing tuber formation than applying the combination of PGR and retardant, especially at high temperature [11].…”
Section: Introductionmentioning
confidence: 87%
“…The positive effects of cytokinin on potato tuberization has also been reported by [9] and [10]. Furthermore, in vitro experiment showed that applying a single plant growth regulator (PGR), has been reported to be less effective in inducing tuber formation than applying the combination of PGR and retardant, especially at high temperature [11].…”
Section: Introductionmentioning
confidence: 87%